2015
DOI: 10.3389/fbioe.2015.00040
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Bound Protein Gradients to Study Haptotaxis

Abstract: Cells navigate in response to inhomogeneous distributions of extracellular guidance cues. The cellular and molecular mechanisms underlying migration in response to gradients of chemical cues have been investigated for over a century. Following the introduction of micropipettes and more recently microfluidics for gradient generation, much attention and effort was devoted to study cellular chemotaxis, which is defined as guidance by gradients of chemical cues in solution. Haptotaxis, directional migration in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 73 publications
0
40
0
1
Order By: Relevance
“…Our migration data is significant because RBG glia were initially only believed able to migrate into the eye disk via physical mechanisms of haptotaxis, i.e. crawling along a substrate (Haeger et al, 2015; Ricoult et al, 2015). However, more recent work suggested abilities of RBG to migrate toward differentiating photoreceptors without using a continuous physical substratum (Rangarajan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Our migration data is significant because RBG glia were initially only believed able to migrate into the eye disk via physical mechanisms of haptotaxis, i.e. crawling along a substrate (Haeger et al, 2015; Ricoult et al, 2015). However, more recent work suggested abilities of RBG to migrate toward differentiating photoreceptors without using a continuous physical substratum (Rangarajan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Adhesive haptotaxis is therefore directly explained by a tug of war in the cell adherence zone, areas with lower grip destabilizing spontaneously under traction in favor to areas with a higher grip (17). In contrast, amoeboid cells migrate at high speed with low adhesion and low traction forces transferred to the substrate(23- 25). A tug of war mechanism, with an interplay of strong adhesion and high traction, is therefore not applicable to amoeboid cells, and the existence of adhesive haptotaxis for leukocytes remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Passive diffusion of a chemoattractant across a porous membrane has also been used to create local gradients in the absence of flow (Dupin et al, 2013). Furthermore, imprinting of protein gradients on rigid substrates (Ricoult et al, 2015;Wu et al, 2011) or controlled stenciling and/or photo-immobilization techniques (Bélisle et al, 2009(Bélisle et al, , 2012Strale et al, 2016) has revealed the molecular basis for haptotaxis, the migration of cells along an ECM gradient. In addition, the use of 3D matrix hydrogels containing smooth gradients of crosslinking density (i.e.…”
Section: Cell Migrationmentioning
confidence: 99%